Kingsman : the secret service [videorecording (Blu-Ray)] - Vaughn, Matthew, 1971-; Firth, Colin, 1960-; Egerton, Taron, 1989-; Jackson, Samuel L.; Caine, Michael; Millar, Mark (20th Century Fox Home Entertainment, 2015)
A super-secret spy organization recruits an unrefined but promising street kid into the agency's ultra-competitive training program just as a global threat emerges from a twisted tech genius.